Measuring disability in amyotrophic lateral sclerosis/motor neuron disease: the WHODAS 2.0-36, WHODAS 2.0-32, and WHODAS 2.0-12. Issue 1 (2nd January 2023) - Young, Carolyn A.; Ealing, John; McDermott, Christopher J.; Williams, Tim L.; Al-Chalabi, Ammar; Majeed, Tahir; Talbot, Kevin; Harrower, Timothy; Faull, Christina; Malaspina, Andrea; Annadale, Joe; Mills, Roger J.; et al.
Abstract: Aim: To investigate whether the World Health Organization Disability Assessment Schedule 2.0 (WHODAS) can provide interval level measurement of disability in Amyotrophic Lateral Sclerosis (ALS), allowing parametric analyses. Methods : Data on the WHODAS 12, 32, and 36-item versions, from 1120 patients studied at one or more time points, were fit to the Rasch model and comparisons made against ALSFRS-R, King's staging, and mortality. Trajectory modeling was undertaken for a newly diagnosed (≤6 months) cohort of 454 individuals. Results : Total scores for WHODAS 32 and 36-item versions can be converted to interval level measurement suitable for individual clinical use, and the 12-item WHODAS total for group use. The 36-item version is shown to be equivalent to the 32-item version. Expected correlations were seen with King's staging, ALSFRS-R, and EQ-5D-5L. Trajectory analysis of disability (WHODAS 2.0) showed three clearly demarcated groups with differences in King's staging, depressive symptomatology and mortality, but not age. Conclusions : The WHODAS 2.0 is a brief patient reported outcome measure which can be used to measure disability in ALS. Provided the patient answers all 36 (32 if not working) items, the conversion table produces an interval level estimate for parametric analyses. The different trajectories demonstrated from diagnosis support the concept of a prodromal period, and suggest the WHODAS 2.0 could be used for surveillance of at risk populations, such as those with genetic predisposition.